2021
DOI: 10.1128/jcm.02889-20
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Genome-Based Gene-by-Gene Typing System for Standardized High-Resolution Strain Typing of Bacillus anthracis

Abstract: Whole-genome-sequencing (WGS) has been established for bacterial subtyping and is regularly used to study pathogen transmission, to investigate outbreaks, and to perform routine surveillance. Core genome multilocus sequence typing (cgMLST) is a bacterial subtyping method that uses WGS data to provide a high resolution strain characterisation. This study aimed at developing a novel cgMLST scheme for Bacillus anthracis, a notorious pathogen that causes anthrax in livestock and humans worldwide. The scheme compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 46 publications
(85 reference statements)
3
39
0
Order By: Relevance
“…Supplementary Figure 2 illustrates the congruence between MLVA31 and wgSNP with one minor exception: the three MLVA31 genotypes constituting MLVA31 clonal complex CC01 ( Supplementary Figure 1 MLVA31 genotypes 1, 2, and 3) belong to different “STI” sublineages separated by almost 100 SNPs. The eight redundant control strains (black dots) are located at zero up to five SNPs from their “sister” strain (same outbreak and same MLVA31 genotype) as is typical for strains from the same outbreak ( Vergnaud, 2020 ; Abdel-Glil et al, 2021 ). In the five events (open dots, events 04, 10, 11, 15, 17) showing two MLVA31 genotypes differing at only one locus, the strains are less than three SNPs apart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Figure 2 illustrates the congruence between MLVA31 and wgSNP with one minor exception: the three MLVA31 genotypes constituting MLVA31 clonal complex CC01 ( Supplementary Figure 1 MLVA31 genotypes 1, 2, and 3) belong to different “STI” sublineages separated by almost 100 SNPs. The eight redundant control strains (black dots) are located at zero up to five SNPs from their “sister” strain (same outbreak and same MLVA31 genotype) as is typical for strains from the same outbreak ( Vergnaud, 2020 ; Abdel-Glil et al, 2021 ). In the five events (open dots, events 04, 10, 11, 15, 17) showing two MLVA31 genotypes differing at only one locus, the strains are less than three SNPs apart.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its strict clonality, the population structure of B. anthracis is conveniently reflected by canonical Single Nucleotide Polymorphism (canSNP) assignment ( Keim et al, 2004 ; Van Ert et al, 2007 ; Sahl et al, 2016 ). Alternative schemes have recently being proposed, including a core genome multilocus sequence typing (cgMLST) approach benefiting from software developed for recombining pathogens ( Abdel-Glil et al, 2021 ) or even a complete renaming inspired by the nomenclature used for Mycobacterium tuberculosis ( Bruce et al, 2020 ). While the cgMLST approach may be convenient for the automated, first-level assignment of whole genome sequence data, the proposition of a full renaming does not bring detectable added value compared to the currently used nomenclature ( Sahl et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genomes of strains BF-1 and BF-5 differ by only three chromosomal SNPs ( Table 1 ). A recent genomic study on an anthrax outbreak in Italy found strains differing by up to five SNPs ( 39 ). Genome analysis for epidemiological investigation of strains associated with injectional anthrax led the authors to the conclusion that genetic variation is possibly generated as a result of infection of a single host.…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of strains BF-1 and BF-5 differ by only three chromosomal SNPs (Table 1). A recent genomic study on an anthrax-outbreak in Italy found strains differing by up to five SNPs [37]. Genome analysis for epidemiologic investigation of strains associated with injectional anthrax have led the authors to the conclusion that genetic variation is possibly generated as a result of infection of a single host but some phylogenetic patterns might be best explained by diversity introduced through several infection-cycles of B. anthracis in several hosts [8].…”
Section: Discussionmentioning
confidence: 99%